El Excentrico, 1954-02-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
February 5, 1954 [5 de febrero de 1954]. Anos 4, No. 7. Cover has a illustration of Abraham Lincoln, the 16th president of the United States. The headline reads, "El Emancipador."